O nexo de causalidade na responsabilidade civil contemporânea - Pascini, Líliam Regina (2012)
The present study aims to discuss the need to review the importance of analyzing Cause as one of the necessary prerequisites for setting civil liability, due the current personalistic characteristics of this legal institution. Through the analysis of the main existing theories about Cause, it´s possible to verify the possibility of its presumption in certain situations of diffuse damage where, despite the difficulty of proof production related to Cause, there is the presence of statistic and logical probability that the cause of harm was originated by a certain agent, becoming forcible, due to the current outlook of civil liability and its base principles particularly the principles of the human dignity and social solidarity the imputation on the duty to indemnify